N. F. S. Grundtvigs breve til hans hustru under Englandsrejsen 1843 - Fabricius, Jørgen (Grundtvig-Studier, 1952)
<span lang="EN-US" style="color: black; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA; mso-bidi-font-style: italic;">N. F. S. Grundtvig s Letters to his Wife during his Visit to England in 1843. By Jørgen Fabricius. <span lang="EN-US" style="color: black; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA; mso-bidi-font-style: italic; mso-bidi-font-weight: bold;">Immediately after Whitsun, 1843, Grundtvig, together with his son Svenn, set forth on his fourth and last journey to England, for which he had been granted a travel bursary by the King through Queen Caroline Amalie. While on his former visits (1829—31) the study of the old Anglo-Saxon manuscripts had been Grundtvig’s chief aim, his principal interest in 1843 was to obtain a first-hand impression of the state of things in the Church in England at the time, and, besides, he hoped to find in England a fruitful soil for his own theories about the Church and thereby to help to lead the Oxford Movement away from a line of development which he thought would inevitably lead its adherents over to Catholicism. <span lang="EN-US" style="color: black; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA; mso-bidi-font-style: italic; mso-bidi-font-weight: bold;">Until now, information about Grundtvig’s own experiences and impressions during this visit could be found only in his letters to Queen Caroline Amalie, and his letters to his wife were not generally known until these were recently discovered in private ownership and have now been published here. <span lang="EN-US" style="color: black; line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-language: AR-SA; mso-bidi-font-style: italic; mso-bidi-font-weight: bold;">Unfortunately these letters give only comparatively scanty information about the actual content of the conversations which Grundtvig had with the various English and Scottish theologians, including Pusey, Newman and Chal97 mers; but they make up for that by giving numerous details of the names of people whom Grundtvig met during his trip, and an account, sometimes almost in diary form, of the course of the trip itself, which may be summarised as follows: June 7th. Departure from Copenhagen. June 12th. Arrival in London, where Grundtvig’s friend, Mr. Nugent Wade, had made arrangements for his visit. June 19th to 29th. Grundtvig’s first stay in Oxford, where he was also accompanied by Wade and had several conversations with Pusey and Newman, among others. June 29th to July 24th. In London again, where Grundtvig spent a good deal of time studying in the Library of the British Museum and was also occupied in visiting various people, including some whose acquaintance he had made on his previous trips to England. On July 24th Grundtvig with Svenn and Wade travelled once more to Oxford, where he again had many conversations, especially with the younger adherents of the Oxford Movement. On July 31st the party left Oxford and, after travelling through Westmoreland and Cumberland as tourists, arrived in Edinburgh on August 6th. Here Grundtvig had one conversation with Chalmers, but when Wade became ill they started on their return journey to London as early as August 10th and arrived there on the 14th. After a fairly long stay in London, during which he made preparations for his journey home which included extensive purchases of books, Grundtvig and his son left England on Sept. 1st and were back in Copenhagen on Sept. 7th, the day before Grundtvig’s 60th birthday.